Strategic thinking during a period of turbulence : a case study of the BancABC Zimbabwe - Mberi, Mary-Jane (Rhodes University, Faculty of Commerce, Rhodes Business School, 2015)
A review of strategic thinking literature indicates that research has tended to focus on experiences contributing to strategic thinking, the strategic thinking perspectives that executives are likely to follow based on the environments in which they have developed their strategic competencies, and examining executives' cognitive maps within the context of strategic management (O' Shannassy 2003; Kutschera, and Ryan, 2009; Meyer, 2007). As an expansion of these principles and foundations of strategic thinking, this research was a study of the extent to which strategic thinking perspectives are utilised during macro environmental turbulence. According to Cravens et al. (2009: 31) volatility, reinvention, and fundamental changes in markets present unprecedented challenges to researchers and executives. "Unfortunately, too often traditional conceptual models and theories fail to provide adequate insight for coping with this new and rapidly changing business environment. Traditional market perspectives and conceptual logic may even blind researchers and strategic decision makers to the real threats present in the changing competitive landscape and new market space, and to opportunities for added value which can be uncovered and exploited" Cravens et al. (2009: 31). Hyperinflation in Zimbabwe was a major problem from 2003 to April 2009, when the country suspended its own currency and for the next five years the country continued to struggle with various macro environmental challenges. It is this backdrop that makes this research intriguing, where the soundness of any organisation is said to be crucially linked to the soundness of the macro environment, including macroeconomic policies as well as internal governance, market discipline; regulation and supervision (Louw and Venter, 2010). The research was a case study of BancABC Zimbabwe and focused on the period 2009 to 2013. BancABC Zimbabwe is a subsidiary of ABC Holdings Limited which is listed on the Botswana and Zimbabwe stock exchanges (BancABC, 2012). The aim of the study as the first key activity was to explore and describe how the BancABC executives responded to the critical macro environmental incidents identified, at a management or executive team perspective, and secondly, whether the rational reasoning or generative reasoning perspective was dominant during the period of turbulence. The goal is to gain insights of the strategic thinking process followed by executives during a period of macro-environmental turbulence. Literature defines strategic thinking concept as the cognitive process undertaken by executives in relation to problem solving in the business context. Two main perspectives are discussed: Strategic thinking as a science (rational thinking) is the prescriptive, structured nature of strategic thinking; arguments are that it is a less complex perspective for executives to adopt. Strategic thinking as an art (generative thinking) is the perspective that allows the strategist to think outside the box and be more creative about solving strategic problems. The discussion presents how the two perspectives can be used to complement each other and provide a more robust strategic thinking framework. The multi-perspective approach to strategic thinking recommends the right balance between analysis, intuition and creativity can be used to create new frameworks and innovative solutions. The ability to balance these strategic thinking perspectives enables executives to solve strategic problems (Linkov, 1999). The research findings highlighted the effect of time and availability of information on the strategic thinking perspective adopted by executives during times of uncertainty. It was noted that when time and information were available, executives appeared to use the rational strategic thinking perspective, while if there was limited time and information to solve problems the generative thinking perspective was dominantly used. Further the importance of integrative strategic thinking which facilitates the use of both intuition and analysis when solving strategic problems in a turbulent macro environment was also highlighted. The research thesis adopted the structure of a case study, relying on the critical incident technique to create the context of the study; and can be used to explore and discuss strategic thinking for teaching purposes. The results of the study can be recognised as a contribution towards the development of strategic thinking particularly in times of turbulence. It can also form the basis for future studies in the context of strategic thinking.
Keywords: BancABC (Zimbabwe); Strategic planning -- Case studies; Strategic planning -- Zimbabwe; Inflation (Finance) -- Zimbabwe; Problem solving -- Zimbabwe; Crisis management -- Zimbabwe; Decision making -- Zimbabwe; Critical incident technique